Balloon pulmonary angioplasty: are we there yet? Lessons learned and unanswered questions. Issue 4 (10th January 2023) - Jevnikar, Mitja; Bokan, Aleksandar; Gille, Thomas; Bertoletti, Laurent; Lichtblau, Mona
Evidence supporting the use of balloon pulmonary angioplasty #BPA, which has drastically changed management of non-operable chronic thromboembolic pulmonary hypertension #CTEPH, and rationale for a future multimodal approach with combined medical therapy https://bit.ly/3F7ccKD